Transformasi Struktural Ekonomi Regional Indonesia Pasca-COVID-19: Pergeseran Sektoral dan Analisis Kebijakan Pemulihan - Rahmat Rafinzar; Januar Eko Aryansah; Riza Adelia Suryani; Novia Kencana (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
The COVID-19 pandemic has significantly altered Indonesia’s regional economic structure, with varying impacts across provinces. This study analyzes changes in the contribution of economic sectors to the Gross Regional Domestic Product (GRDP) of Indonesian provinces from 2020 to 2024, focusing on sectors directly affected by the pandemic. The research employs a content analysis approach using sectoral GRDP data from the Central Statistics Agency and relevant literature. The findings indicate shifts in sectoral dominance, including the rapid expansion of digitalization across regions, while traditional sectors such as tourism experience slower recovery. Technology-based and natural resource–based sectors demonstrate greater resilience to pandemic-related disruptions. These results highlight the importance of adaptive economic policies in supporting structural transformation at the regional level. The study provides insights for designing more inclusive and sustainable Post-COVID-19 recovery strategies, particularly by strengthening resilient sectors and facilitating the transition of vulnerable sectors within Indonesia’s evolving regional economic landscape.